Aerogel

A polyfunctional acrylate-based airgel with controlled surface area and crosslinked structure addresses the limitations of conventional materials by enhancing mechanical strength and thermal properties, ensuring stability and transparency.

JP2025007263APending Publication Date: 2025-01-17THE INSTITUTE OF PHYSICAL & CHEMICAL RESEARCH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023108542
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional polycondensation-based organic porous materials suffer from issues such as coloration, decreased transparency over time, and pore diameters larger than 1 μm, leading to poor mechanical strength and thermal properties.

Method used

The use of a polyfunctional acrylate with 3 or 4 acrylic groups in one molecule, combined with a specific surface area of 100-800 m²/g, forms a crosslinked airgel with improved mechanical strength and thermal properties through radical polymerization and controlled drying processes.

Benefits of technology

The resulting airgel exhibits excellent mechanical strength, thermal stability, and low thermal conductivity, making it suitable for high-temperature applications with minimal shrinkage and defect-free pore structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007263000001
    Figure 2025007263000001
Patent Text Reader

Abstract

To provide a laminate with superior mechanical properties and heat properties.SOLUTION: An aerogel has a repeating unit derived from a polyfunctional acrylate having three or four acrylic groups in one molecule, with a BET specific surface area of 100 m2 / g or more and 800 m2 / g or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aerogel. [Background technology]

[0002] It is known that when the size of the particles forming the porous body and the size of the voids formed between the particles are smaller than the wavelength of the incident light, the light passes through the porous body without being scattered at the interface. It is also known that the dielectric constant and refractive index are reduced without changing the composition of the matrix because air is introduced into the matrix. As organic porous bodies having such properties, for example, an organic aerogel obtained by supercritical drying of an organic wet gel synthesized by polycondensation of resorcinol and formaldehyde (Patent Document 1 below), an organic aerogel using melamine-formaldehyde (Patent Document 2 below), a polyisocyanate-based aerogel obtained by a similar method (Patent Document 3 below), and a porous body obtained by supercritical drying of a gel obtained by copolymerization of methyl methacrylate and ethylene glycol dimethacrylate (Patent Document 4 below) are known.

[0003] Conventionally known polycondensation-based organic porous materials have problems such as being significantly colored deep red and losing transparency over time, and organic porous materials obtained from methyl methacrylate and ethylene glycol dimethacrylate have problems such as a pore size of 1 μm or more and a lack of transparency.

[0004] The supercritical drying method, in which a porous body is obtained by supercritical drying of a wet gel, is known as a method for producing a porous body with high porosity (see Patent Document 5 below). However, the supercritical drying method has room for improvement from the viewpoint of stable mass production of aerogel, and there has been a demand for an aerogel with excellent mass-producibility. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] U.S. Pat. No. 4,873,218 [Patent Document 2] U.S. Patent No. 5,086,085 [Patent Document 3] WO 95 / 03358 [Patent Document 4] U.S. Patent No. 5,252,620 [Patent Document 5] International Publication No. 2021 / 132296 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an aerogel having excellent mechanical strength and thermal properties. [Means for solving the problem]

[0007] The invention made to solve the above problems is a polyolefin polymer having a repeating unit derived from a multifunctional acrylate having 3 or 4 acrylic groups in one molecule, and a BET specific surface area of ​​100 m 2 / g or more 800m 2 / g or less. Effect of the Invention

[0008] The aerogel of the present invention has excellent mechanical strength and thermal properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The laminate of the present invention will be described in detail below.

[0010] <Aerogel> The aerogel has a repeating unit derived from a multifunctional acrylate having 3 or 4 acrylic groups in one molecule, and has a BET specific surface area of ​​100 m 2 / g or more 800m 2 / g or less.

[0011] The aerogel has excellent mechanical strength and thermal properties. The reason why the aerogel has the above-mentioned structure and thus exhibits the above-mentioned effects is not necessarily clear, but is presumed to be, for example, as follows. That is, by using a multifunctional acrylate having three or four acrylic groups in one molecule, (1) a high-strength gel is formed, so that the aerogel after drying also has excellent mechanical strength, and (2) shrinkage during drying is suppressed, so that the BET specific surface area is large and the pore volume is increased, so that the thermal properties are excellent.

[0012] The aerogel is a polymer obtained by radical polymerization of the polyfunctional acrylate, and has a three-dimensional network structure (crosslinked structure) and pores. The aerogel can be produced by using an aerogel-forming composition described later.

[0013] In this specification, the term "polyfunctional" is used to mean having multiple acrylic groups, for example, a "bifunctional acrylate" means a compound having two acrylic groups, and the term "monofunctional" is used to mean having one acrylic group.

[0014] Examples of polyfunctional acrylates having three acrylic groups in one molecule (trifunctional acrylates) include trimethylolpropane triacrylate, pentaerythritol triacrylate, tris(2-acryloyloxyethyl) isocyanurate, glycerin triacrylate, and succinic acid-modified pentaerythritol triacrylate.

[0015] Examples of polyfunctional acrylates having four acrylic groups in one molecule (tetrafunctional acrylates) include pentaerythritol tetraacrylate and ditrimethylolpropane tetraacrylate.

[0016] As the polyfunctional acrylate having three or four acrylic groups in one molecule, a tetrafunctional acrylate is preferable, and pentaerythritol tetraacrylate is more preferable, which leads to a higher crosslink density and thus improved mechanical strength and thermal properties.

[0017] The aerogel preferably further contains a repeating unit derived from at least one selected from the group consisting of a monofunctional acrylate having one acrylic group in one molecule and a bifunctional acrylate having two acrylic groups in one molecule, which can impart functionality such as hydrophobicity and can also adjust the physical properties.

[0018] Examples of monofunctional acrylates having one acrylic group per molecule include 1,1,1,3,3,3-hexafluoroisopropyl acrylate, isobornyl acrylate, dicyclopentanyl acrylate, cyclohexyl acrylate, hexyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, decyl acrylate, dodecyl acrylate, stearyl acrylate, trifluoroethyl acrylate, heptadecafluorodecyl acrylate, trimethylsilyl acrylate, tetrahydrofurfuryl acrylate, ethoxydiethylene glycol acrylate, benzyl acrylate, phenoxyethyl acrylate, polyethylene glycol monoacrylate, and polypropylene glycol monoacrylate.

[0019] Examples of bifunctional acrylates having two acrylic groups in one molecule include ethylene glycol diacrylate, 1,3-propanediol diacrylate, 1,4-butanediol diacrylate, neopentyl glycol diacrylate, 3-methyl-1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tricyclo[5.2.1.0]phenyl diacrylate, and 1,2,3,4-tetramethylphenyl diacrylate. 2,6 ] decanedimethanol diacrylate, polyethylene glycol diacrylate (number of repeating ethylene glycol units: 4 to 15), and polypropylene glycol diacrylate (number of repeating propylene glycol units: 4 to 15).

[0020] The BET specific surface area of ​​the aerogel is 100m 2 / g or more 800m 2 The BET specific surface area of ​​the aerogel can be measured by the measurement method described in the Examples below.

[0021] The lower limit of the BET specific surface area is 100 m 2 / g, 200m 2 / g is preferred, and 300m 2 / g, more preferably 350. The upper limit of the BET specific surface area is 800 m 2 / g, 700m 2 / g is preferred, and 600m 2 / g is more preferable, and 500m 2 / g is more preferred.

[0022] The density of the aerogel is 0.05 g / cm 3 More than 0.30g / cm 3 The density in the above range can further improve the mechanical strength and thermal properties. The lower limit of the density is preferably 0.05 g / cm. 3 is preferred, and 0.10 g / cm 3 More preferably, 0.20 g / cm 3 More preferably, 0.21 g / cm 3 In some cases, the upper limit of the density is preferably 0.30 g / cm. 3 is preferred, and 0.29 g / cm 3 More preferably, 0.27 g / cm 3 The density can be measured by the method described in the Examples below.

[0023] The lower limit of the pore volume of the aerogel is 0.3 cm 3 / g is preferred, and 0.4 cm 3 / g is more preferable, and 0.5 cm 3 / g may be preferred. The upper limit of the pore volume is 1.5 cm 3 / g is preferred, and 1.0 cm 3 / g is more preferable, and 0.9 cm 3 / g is more preferable, and 0.8 cm 3 / g may be preferable. When the pore volume is in the above range, the mechanical properties of the aerogel are further improved. The pore volume can be measured by the measurement method described in the Examples below.

[0024] The aerogel preferably has a decomposition start temperature of TG-DTA under nitrogen of 250° C. or higher and 400° C. or lower. In this case, the aerogel can be used as a member that can be used in a high-temperature environment.

[0025] The thermal conductivity of the aerogel is preferably less than 0.05 W / mK. When the thermal conductivity of the aerogel is within the above range, it can be used as a thermal management material. The lower limit of the thermal conductivity is preferably 0.020 W / mK, more preferably 0.025 W / mK. The upper limit of the thermal conductivity is preferably 0.05 W / mK, more preferably 0.045 W / mK. The thermal conductivity can be measured by the measurement method described in the Examples below.

[0026] The compressive strength of the aerogel is preferably 5 MPa or more and 100 MPa or less. When the compressive strength of the aerogel is in the above range, it can be used for a long period of time as a member that is subjected to high external stress. The compressive strength can be measured by the measurement method described in the Examples below.

[0027] The diameter of the pores in the aerogel is preferably 1 nm or more and 500 nm or less.

[0028] <Aerogel-forming composition> The aerogel-forming composition contains a polyfunctional acrylate having 3 or 4 acrylic groups in one molecule (hereinafter also referred to as "polyfunctional acrylate [A]"), a radical photopolymerization initiator (hereinafter also referred to as "radical photopolymerization initiator [B]"), and a solvent having a boiling point of 100°C or more and 300°C or less under atmospheric pressure (hereinafter also referred to as "solvent [C]"). The aerogel-forming composition may contain other components (hereinafter simply referred to as "other components") other than the polyfunctional acrylate [A], the radical photopolymerization initiator [B], and the solvent [C], as necessary, within a range that does not impair the effects of the present invention.

[0029] According to the above-mentioned aerogel-forming composition, an aerogel having excellent mechanical properties and thermal properties can be formed. The reason is not necessarily clear, but it is presumed to be as follows. [A] in the insulating film-forming composition is a multifunctional acrylate having 3 or 4 acrylic groups in one molecule, and by radical polymerization in a solvent with a relatively low boiling point, an aerogel having few defects in the crosslinked structure and having pores of a certain size can be obtained. It is believed that the excellent mechanical properties and thermal properties are exhibited by the fact that air is packed into the pores of this polymer aerogel.

[0030] The solid content concentration of the aerogel-forming composition is preferably 5% by mass or more and 35 parts by mass or less. When the solid content concentration is within the above range, an aerogel with a high pore volume can be obtained. The lower limit of the solid content concentration is preferably 5% by mass, more preferably 10% by mass, and even more preferably 15% by mass. The upper limit of the solid content concentration is preferably 35% by mass, more preferably 30% by mass, and even more preferably 25% by mass. The solid content concentration means the concentration of all components other than the solvent [C] contained in the aerogel-forming composition.

[0031] Each component contained in the aerogel-forming composition will be described below.

[0032] [[A] Multifunctional acrylate] The multifunctional acrylate [A] is a multifunctional acrylate having three or four acrylic groups in one molecule, and is described above in the section <Aerogel>. The aerogel-forming composition may contain a monofunctional acrylate or a bifunctional acrylate in addition to the multifunctional acrylate [A]. These are also described above in the section <Aerogel>. The aerogel-forming composition may contain one or more types of multifunctional acrylate [A] in combination. The lower limit of the content of the polyfunctional acrylate [A] in the aerogel-forming composition is preferably 5% by mass, more preferably 9% by mass, and even more preferably 12% by mass. The upper limit of the content is preferably 30% by mass, more preferably 25% by mass, and even more preferably 20 parts by mass. By setting the content within the above range, an aerogel having excellent mechanical strength can be produced.

[0033] [[B] Radical photopolymerization initiator] The radical photopolymerization initiator [B] may be a compound capable of generating an active species capable of initiating a radical polymerization reaction of the polyfunctional acrylate [A] upon exposure to radiation such as visible light, ultraviolet light, far ultraviolet light, electron beams, X-rays, etc. The radical polymerization initiator [B] may be used alone or in combination of two or more kinds.

[0034] By exposing the coating of the aerogel-forming composition to light, radicals are generated from the radical photopolymerization initiator [B], and the crosslinking reaction of the polyfunctional acrylate [A] progresses, thereby accelerating curing and forming an aerogel.

[0035] Specific examples of the radical photopolymerization initiator [B] include O-acyloxime compounds, α-aminoketone compounds, α-hydroxyketone compounds, and acylphosphine oxide compounds.

[0036] Examples of the O-acyloxime compound include 1-[9-ethyl-6-(2-methylbenzoyl)-9.H.-carbazol-3-yl]-ethan-1-one oxime-O-acetate, 1-[9-ethyl-6-benzoyl-9.H.-carbazol-3-yl]-octan-1-one oxime-O-acetate, 1-[9-ethyl-6-(2-methylbenzoyl)-9.H.-carbazol-3-yl]-octan-1-one oxime-O-acetate, yl]-ethan-1-one oxime-O-benzoate, 1-[9-n-butyl-6-(2-ethylbenzoyl)-9.H.-carbazol-3-yl]-ethan-1-one oxime-O-benzoate, ethanone,1-[9-ethyl-6-(2-methyl-4-tetrahydrofuranylbenzoyl)-9.H.-carbazol-3-yl]-,1-(O-acetyl oxime), ethanone,1-[9-ethyl -6-(2-methyl-4-tetrahydropyranylbenzoyl)-9.H.-carbazol-3-yl]-, 1-(O-acetyloxime), ethanone, 1-[9-ethyl-6-(2-methyl-5-tetrahydrofuranylbenzoyl)-9.H.-carbazol-3-yl]-, 1-(O-acetyloxime), ethanone, 1-[9-ethyl-6-{2-methyl-4-(2,2-dimethyl-1,3-dihydro xolanyl)methoxybenzoyl}-9.H.-carbazol-3-yl]-, 1-(O-acetyloxime), ethanone, 1-[9-ethyl-6-(2-methyl-4-tetrahydrofuranylmethoxybenzoyl)-9.H.-carbazol-3-yl]-, 1-(O-acetyloxime), 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)].

[0037] Examples of the α-aminoketone compound include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one.

[0038] Examples of the α-hydroxyketone compound include 1-phenyl-2-hydroxy-2-methylpropan-1-one, 1-(4-i-propylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, and 1-hydroxycyclohexylphenyl ketone.

[0039] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

[0040] As the radical photopolymerization initiator [B], from the viewpoint of further promoting the curing reaction by radiation, an O-acyloxime compound or an acylphosphine oxide compound is preferable, and 1-[9-ethyl-6-(2-methylbenzoyl)-9.H.-carbazol-3-yl]-ethan-1-one oxime-O-acetate, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide is more preferable.

[0041] When the aerogel-forming composition contains a radical polymerization initiator, the lower limit of the content of the radical photopolymerization initiator [B] is preferably 0.1 parts by mass, more preferably 0.5 parts by mass, and even more preferably 1 part by mass, relative to 100 parts by mass of the polyfunctional acrylate [A]. The upper limit of the content is preferably 20 parts by mass, more preferably 10 parts by mass, and even more preferably 5 parts by mass, relative to 100 parts by mass of the polyfunctional acrylate [A]. By setting the content within the above range, the curing reaction by radiation can be further promoted.

[0042] [[C] Solvent] The solvent [C] has a boiling point of 100°C or higher and 300°C or lower under atmospheric pressure (1 atm). By using a solvent with a boiling point in a specific range, it is not necessary to dry at high temperature and high pressure, so that an aerogel with excellent mechanical strength can be produced while maintaining the pore structure. The solvent [C] can be used alone or in combination of two or more types.

[0043] The lower limit of the boiling point of the solvent [C] is 100° C., more preferably 120° C., and still more preferably 150° C. The upper limit of the boiling point is 300° C., more preferably 250° C., and still more preferably 230° C.

[0044] [C] Examples of the solvent include aromatic hydrocarbon solvents such as diethylene glycol monoethyl ether acetate, diethylene glycol diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, propylene glycol monomethyl ether, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, cyclohexanol acetate, benzyl alcohol, 3-methoxybutanol, toluene, and xylene. These solvents can be used alone or in combination of two or more. Among these solvents, aromatic hydrocarbon solvents such as toluene and xylene are particularly preferred because they can achieve a high level of both mechanical strength and pore volume of the aerogel.

[0045] [Other ingredients] Examples of other components include an adhesion aid, a surfactant, and a polymerization inhibitor.

[0046] Examples of adhesion aids include trimethoxysilylbenzoic acid, vinyltriacetoxysilane, vinyltrimethoxysilane, γ-isocyanatepropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylalkyldialkoxysilane, γ-chloropropyltrialkoxysilane, γ-mercaptopropyltrialkoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0047] When the aerogel-forming composition contains an adhesion aid, the content of the adhesion aid is preferably 20 parts by mass or less, and more preferably 1 part by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the polyfunctional acrylate [A]. When the content of the adhesion aid is within the above range, the adhesion between the base and the insulating film to be formed is improved.

[0048] Examples of the surfactant include fluorine-based surfactants and silicone-based surfactants. When the aerogel-forming composition contains a surfactant, the content of the surfactant is preferably 1 part by mass or less, more preferably 0.01 parts by mass or more and 0.6 parts by mass or less, relative to 100 parts by mass of the polyfunctional acrylate [A].

[0049] The polymerization inhibitor is a component that suppresses the cleavage of the molecules of the polyfunctional acrylate [A] by capturing radicals generated by exposure or heating, or by decomposing peroxides generated by oxidation. When the aerogel-forming composition contains a polymerization inhibitor, the degradation due to cleavage of the polymer molecules in the insulating film to be formed is suppressed, and the light resistance of the aerogel can be improved.

[0050] Examples of the polymerization inhibitor include hindered phenol compounds, hindered amine compounds, alkyl phosphite compounds, and thioether compounds. Among these, hindered phenol compounds are preferred.

[0051] When the aerogel-forming composition contains a polymerization inhibitor, the content of the polymerization inhibitor is preferably 1 part by mass or less, and more preferably 0.01 to 0.6 parts by mass, per 100 parts by mass of the polyfunctional acrylate [A].

[0052] <Aerogel manufacturing method> The method for producing an aerogel includes a step of irradiating (exposing) an aerogel-forming composition with radiation to obtain a gel (hereinafter also referred to as a "gel-forming step"), and a step of drying the gel (hereinafter also referred to as a "drying step").

[0053] According to the method for producing an aerogel, an aerogel having excellent thermal and mechanical properties can be produced. Each step will be described below.

[0054] [Gel formation process] In this step, the aerogel-forming composition is irradiated (exposed) to radiation to form a gel by a photocuring reaction. The reaction conditions for the photocuring reaction are not particularly limited as long as a gel can be obtained, and the reaction temperature, reaction time, etc. can be in the same range as those for conventional gels. The photocuring reaction is preferably carried out under an inert gas atmosphere such as nitrogen or argon. Generally, the radiation can be, for example, visible light, ultraviolet light, far ultraviolet light, electron beams, X-rays, etc. Among these radiations, radiation with a wavelength in the range of 190 nm to 450 nm is preferred, and radiation containing ultraviolet light of 365 nm is more preferred.

[0055] The lower limit of the exposure dose in this process is 10 mJ / cm as a value measured by an illuminometer ("OAI model 356" by OAI Optical Associates Inc.) at a wavelength of 365 nm. 2 is preferred, and 20 mJ / cm 2 The upper limit of the exposure amount is preferably 2,000 mJ / cm as measured by the illuminometer. 2 is preferred, and 1,000 mJ / cm 2 is more preferred. [Drying process] In this step, the formed gel is dried to obtain an aerogel. A known method can be used to dry the gel. For example, atmospheric pressure drying, reduced pressure drying, freeze drying, supercritical drying, etc. can be mentioned, but reduced pressure drying is preferably used. This is because the destruction and shrinkage of the gel skeleton can be suppressed by precisely controlling the conditions of reduced pressure drying. In addition, when drying the gel by supercritical drying, the dispersion medium is removed at a temperature and pressure equal to or higher than the critical point of the dispersion medium of the gel. In the case of supercritical drying, it is preferable to replace the dispersion medium of the gel from the reaction solvent to ethanol and further to liquefied carbon dioxide by performing the above-mentioned solvent replacement. EXAMPLES

[0056] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0057] <Preparation of aerogel> [Example 1] Preparation of aerogel A1 0.54g of pentaerythritol tetraacrylate and 0.016g of 2,2-diethoxyacetophenone were dissolved in 2.46g of toluene, and after bubbling with nitrogen, the solution was sealed in a cylindrical transparent polyethylene container with a diameter of 15mm. The container was irradiated with a 250W high-pressure mercury lamp at room temperature for 30 minutes to obtain a precursor gel. The gel was introduced into a vacuum dryer and dried at 0.03 atmospheric pressure and 40°C for 12 hours to obtain aerogel A1.

[0058] [Example 2] Preparation of aerogel A2 Aerogel A2 was obtained in the same manner as in Example 1 except that the amount of toluene was 2.64 g and the amount of pentaerythritol tetraacrylate was 0.36 g.

[0059] [Example 3] Preparation of aerogel A3 Aerogel A3 was obtained in the same manner as in Example 1, except that 0.54 g of pentaerythritol tetraacrylate was replaced with 0.54 g of ditrimethylolpropane tetraacrylate.

[0060] [Example 4] Preparation of Aerogel A4 Aerogel A4 was obtained in the same manner as in Example 1, except that 0.54 g of pentaerythritol tetraacrylate was replaced by 0.432 g of pentaerythritol tetraacrylate and 0.108 g of tricyclodecane dimethanol diacrylate.

[0061] [Example 5] Preparation of Aerogel A5 Aerogel A5 was obtained in the same manner as in Example 1, except that 0.54 g of pentaerythritol tetraacrylate was replaced with 0.432 g of pentaerythritol tetraacrylate and 0.108 g of 1,1,1,3,3,3-hexafluoroisopropyl acrylate.

[0062] [Example 6] Preparation of aerogel A6 Aerogel A6 was obtained in the same manner as in Example 1, except that 0.54 g of tris(2-acryloyloxyethyl) isocyanurate was used instead of 0.54 g of pentaerythritol tetraacrylate.

[0063] [Example 7] Preparation of aerogel A7 Aerogel A7 was obtained in the same manner as in Example 1, except that 0.54 g of glycerin triacrylate was used instead of 0.54 g of pentaerythritol tetraacrylate.

[0064] [Comparative Example 1] Preparation of aerogel C1 An aerogel C1 was obtained in the same manner as in Example 1, except that 0.54 g of hexamethylene glycol diacrylate was used instead of 0.54 g of pentaerythritol tetraacrylate.

[0065] [Comparative Example 2] Preparation of Aerogel C2 An aerogel C2 was obtained in the same manner as in Example 1, except that 0.54 g of dipentaerythritol hexaacrylate was used instead of 0.54 g of pentaerythritol tetraacrylate.

[0066] [Comparative Example 3] 0.54g of pentaerythritol tetraacrylate and 0.016g of 2,2-diethoxyacetophenone were dissolved in 2.46g of N,N-dimethylformamide (DMF), and after nitrogen bubbling, the solution was sealed in a cylindrical transparent polyethylene container with a diameter of 15mm. The container was irradiated with a 250W high-pressure mercury lamp at room temperature for 30 minutes to obtain a precursor gel. The gel was introduced into a vacuum dryer and dried at 0.03 atmospheric pressure and 80℃ for 12 hours, whereupon cracks occurred.

[0067] <Evaluation> The density, BET specific surface area, pore volume, thermal decomposition temperature, thermal conductivity and compressive strength of the aerogel prepared above were measured according to the following methods.

[0068] [density] The density of the aerogel was measured by measuring its size and mass. For the size measurement, an arbitrary cross section of the aerogel was observed with a scanning electron microscope (SEM) under the following conditions. Sample to be measured: Aerogel was sliced ​​into thin pieces using a razor. Measurement device: Apreo S LoVac (Thermo Fisher Scientific) Measurement conditions: 80 Pa, room temperature

[0069] [BET specific surface area and pore volume] The BET specific surface area of ​​the aerogel was measured by isothermal adsorption of nitrogen gas using a BELSORP18PLUS-HT (manufactured by BEL Japan) according to a standard method. The pore volume was calculated by the GCMC method.

[0070] [Thermal decomposition temperature] Using a high-sensitivity differential thermobalance ("STA 2500 Regulus" manufactured by Netzsch Japan), thermogravimetry of the aerogel was performed according to a standard method, and the 5% weight loss temperature (Td5) was determined as the thermal decomposition temperature.

[0071] [Thermal Conductivity] The thermal conductivity of the aerogel was measured using an ai-Phase Mobile-10 (manufactured by ai-Phase Co., Ltd.) by the temperature wave amplitude method / AC steady-state method.

[0072] [Compressive strength] The compressive strength of the aerogel was measured at break using a universal material testing machine (Instron 5967) at room temperature and a compression speed of 5 mm / min. The measurement sample was a cylindrical sample with the surface shaped with a razor.

[0073] In Table 1 below, the symbols in the column "[A] Multifunctional acrylate" are as follows. (A-1): Pentaerythritol tetraacrylate (number of acrylic groups: 4) (A-2): Ditrimethylolpropane tetraacrylate (number of acrylic groups: 4) (A-3): Tris(2-acryloyloxyethyl)isocyanurate (number of acrylic groups: 3) (A-4): Glycerin triacrylate (number of acrylic groups: 3) (A-5): Tricyclodecane dimethanol diacrylate (number of acrylic groups: 2) (A-6): 1,1,1,3,3,3-hexafluoroisopropyl acrylate (number of acrylic groups: 1) (A-7): Hexamethylene glycol diacrylate (number of acrylic groups: 2) (A-8): Dipentaerythritol hexaacrylate (number of acrylic groups: 6)

[0074] [Table 1]

[0075] From Table 1, it was found that Examples 1 to 7 had lower thermal conductivity and superior compressive strength compared to Comparative Examples 1 and 2. Although a restrictive interpretation is not desired, it is believed that the reason Examples 1 to 7 were able to achieve both lower thermal conductivity and higher compressive strength compared to Comparative Examples 1 and 2 is that the BET specific surface area was increased. It is believed that the use of a multifunctional acrylate with 3 or 4 acrylic groups suppresses shrinkage during drying, thereby increasing the BET specific surface area.

Claims

1. It has a repeating unit derived from a multifunctional acrylate having 3 or 4 acrylic groups in one molecule, and has a BET specific surface area of ​​100 m 2 / g or more 800m 2 / g or less.

2. 2. The aerogel according to claim 1, further comprising a repeating unit derived from at least one selected from the group consisting of a monofunctional acrylate having one acrylic group in one molecule and a bifunctional acrylate having two acrylic groups in one molecule.

3. 2. The aerogel according to claim 1, wherein the polyfunctional acrylate is pentaerythritol tetraacrylate.

4. Density is 0.05 g / cm 3 0.30g / cm or more 3 2. The aerogel of claim 1, wherein:

5. Pore ​​volume is 0.3 cm 3 / g or more 1.5cm 3 2. The aerogel according to claim 1, wherein the molecular weight is 1 / g or less.

6. 2. The aerogel according to claim 1, wherein the decomposition onset temperature in TG-DTA under nitrogen is 250° C. or higher and 400° C. or lower.

7. 10. The aerogel of claim 1, having a thermal conductivity of less than 0.05 W / mK.

8. 2. The aerogel according to claim 1, having a compressive strength of 5 MPa or more and 100 MPa or less.

Citation Information

Patent Citations

  • Low density, resorcinol-formaldehyde aerogels

    US4873218A

  • Melamine-formaldehyde aerogels

    US5086085A

  • Microcellular foams

    US5252620A

  • Organic aerogels

    WO1995003358A1

  • Aerogel and method for producing same

    WO2021132296A1